PERBANDINGAN KARAKTERISTIK MARSHALL PADA CAMPURAN ASPAL PANAS LAPIS BETON LAPIS ANTARA MENGGUNAKAN AGREGAT UKURAN 25 mm DAN AGREGAT UKURAN 19 mm - Milo, Maria Krisanti Ivoni Milo; Kalogo, Egidius; Bela, Krisantos Ria (Eternitas: Jurnal Teknik Sipil, 2023)
The hot mix asphalt-aggregate mixture in the construction of asphalt concrete roads generally consists of three layers: the base layer, intermediate layer, and surface layer placed on a granular subbase. One of the asphalt concrete layers is the Intermediate Layer, which is a hot asphalt mixture consisting of aggregate, asphalt material, and filler mixed at a central mixing plant. The resulting mixture is spread and compacted on the Aggregate Base Layer. The hot asphalt mixture is designed according to the General Specifications for Road and Bridge Construction by the Directorate General of Highways in 2018 (Revision 3) to ensure that the design assumptions regarding Asphalt Content, Air Voids, Stability, Flexibility, and Durability are in line with the planned traffic. Research results indicate differences in Marshall characteristics from Marshall test results for the Intermediate Layer asphalt concrete mixture (AC-BC) of the two compositions. Almost all Marshall properties meet the Directorate General of Highways specifications in 2018 Revision 3, except for Flow with a particle size of 19 mm, which does not meet the specified flow range of 2 – 4 mm, and Marshall Stability for Aggregate Residue with a particle size of 19 mm, which does not meet the specified minimum of 90%. Meanwhile, the Optimum Asphalt Content (OAC) values for Aggregate with a particle size of 25 mm are 5.11%, and for Aggregate with a particle size of 19 mm, it is 5.18%.